2008
DOI: 10.1113/jphysiol.2007.149989
|View full text |Cite
|
Sign up to set email alerts
|

Local calcium release activation by DHPR calcium channel openings in rat cardiac myocytes

Abstract: The principal role of calcium current in the triggering of calcium release in cardiac myocytes is well recognized. The mechanism of how calcium current (I Ca ) controls the intensity of calcium release is not clear because of the stochastic nature of voltage-dependent gating of calcium channels (DHPRs) and of calcium-dependent gating of ryanodine receptors (RyRs). To disclose the relation between DHPR openings and the probability of calcium release, local calcium release activation by I Ca was investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 59 publications
6
49
0
Order By: Relevance
“…Recent studies have demonstrated that there is a "redundancy" of the trigger I Ca in a diad, that is reducing either the number of individual open channel or single channel current alone increases EC coupling gain [36,37]. I Ca is the ensemble of single channel currents (I Ca ) through That NO decreases the conductance and Po of single LCC current as reported in previous studies [38,39] further supports this notion.…”
Section: Mechanisms For Pd Increasing Ec Coupling Efficiencysupporting
confidence: 52%
“…Recent studies have demonstrated that there is a "redundancy" of the trigger I Ca in a diad, that is reducing either the number of individual open channel or single channel current alone increases EC coupling gain [36,37]. I Ca is the ensemble of single channel currents (I Ca ) through That NO decreases the conductance and Po of single LCC current as reported in previous studies [38,39] further supports this notion.…”
Section: Mechanisms For Pd Increasing Ec Coupling Efficiencysupporting
confidence: 52%
“…With regard to biochemical signaling cascades, tiny ∼fA Ca 2+ fluxes, generally believed not to partake in local signaling, could produce ∼μM Ca 2+ signals sufficient to signal locally to molecules like CaM or CaMKII (34). Nanodomain boosting may similarly play a role in the contraction of ventricular myocytes, where controversy exists regarding whether activation of ryanodine receptors can be triggered by the opening of a single Ca V channel [high-fidelity scenario supported by early experimental work (35)(36)(37)(38)], or if the simultaneous opening of ∼10 channels is necessary [as suggested by recent models that take account of the small ∼fA flux through a single Ca V channel at the +50 mV ventricular plateau potential (39)(40)(41)]. Our findings may reconcile this low-flux high-fidelity paradox given that a single Ca V channel would, by virtue of nanodomain Ca 2+ boosting, have the potency of ∼10 channels in the absence of this amplification.…”
Section: Significancementioning
confidence: 99%
“…The third relationship, P trig vs. i Ca , called the 'coupling fidelity' in other studies Altamirano & Bers, 2007;Polakova et al 2008), is not known precisely. However, it stands to reason that P trig will be zero at i Ca = 0 and will reach a saturating level at large values of i Ca .…”
Section: Methodsmentioning
confidence: 99%